A126 SAFETY OF COMBINATION BIOLOGIC AND IMMUNOSUPPRESSIVE THERAPY POST-ORTHOTOPIC LIVER TRANSPLANTATION IN PATIENTS WITH INFLAMMATORY BOWEL DISEASE: A SYSTEMATIC REVIEW. (15th March 2019) - Al Draiweesh, S; Ma, C; Alkhattabi, M; Nguyen, T; Brahmania, M; Jairath, V
Abstract: Background: Inflammatory Bowel Disease (IBD) patients post orthotopic liver transplantation (OLT) often have ongoing mucosal inflammation necessitating biologic agents for therapy. The safety of combined biologic and immunosuppressive therapy post-OLT in this population is unclear. Aims: To systematically review the evidence for safety of combination biologic and immunosuppressive therapy in patients with Primary sclerosing cholangitis (PSC)/other liver diseases and concomitant IBD after OLT. Methods: EMBASE, Medline, Cochrane CENTRAL, clinialtrials.gov, and the International Clinical Trials Registry Platform were searched without language restriction using keywords identifying OLT and IBD up to March 1, 2018. All studies evaluating the safety of combined biologic and anti-rejection therapy were included. All eligible studies were reviewed for safety outcomes, including infections, cancers, death, and colectomy rate. Meta-analysis was not performed due to the low quality of evidence available. Results: A total of 2713 citations were identified: 2315 articles were screened after removal of duplicates (n=399) and we identified 20 articles (12 case series and 8 case reports) that were eligible for inclusion. From these studies, a total of 109 IBD patients were treated with combination biologic and immunosuppressive therapy. PSC was the primary indication for OLT in 87 patients (79.8%) with 67 (61.5%) having ulcerative colitis. TNF antagonists were used in 91 patients (83.5%) while 17 patients (15.5%) received Vedolizumab, and a single patient received ustekinumab. The most commonly used anti-rejection therapies were tacrolimus, prednisone, azathioprine and mycophenolate mofetil. A total of 22 (20.2%) patients experienced an infectious complication (cholangitis (n=3), clostridium difficile (n=3), CMV colitis and viremia (n=1), Post-op infections (n=5), cryptosporidiosis (n=2), bacterial pneumonia (n=1), oral candidiasis (n=1), esophageal candidiasis (n=1), campylobacter (n=1), infectious diarrhea (n=1), enterococcus faecalis bacteremia (n=1), molluscum contagiosum (n=1), wound infections (n=1)). All infections were reported in patients on anti-TNF therapy. Malignancy was reported in 6 patients (5.5%). Four patients had colorectal cancer, one patient had cholangiocarcinoma and one patient had cervical cancer. There were two deaths (CRC and recurrent PSC with cholangitis). Conclusions: Post-OLT IBD patients receiving anti-TNF therapy are at an increased risk of enteric and post-operative infectious complications. Enteric infections should be actively screened for in patients experiencing worsening IBD symptoms. Funding Agencies: None